In vitro antifungal effect of garlic solution (Allium sativum), colloidal oats (Avena sativa) versus clotrimazole on Candida albicans cultures (ATCC 10231), Trujillo, January-October 2016 - Robles-Sánchez, Gleiky Janet (2021)
Introduction: During the last years, sexually transmitted infections (STIs) continue to be a public health problem of great importance in most countries of the world. The incidence of acute STIs is considered high in many countries; Failures in diagnosis and late treatment being the main problem of causing serious complications and sequelae, including infertility, fetal loss, ectopic pregnancy, anogenital cancer and premature death, as well as infections in newborns. and infants. Since the costs of caring for an STI, both at an individual and national level, are considerable, this research is carried out to treat the Candidiasis that so much afflicts the female community in an accessible and natural way. Objective: To test the antifungal effect in vitro of garlic solution (Allium sativum), colloidal oats (Avena sativa) versus Clotrimazole in the growth of Candida albicans strains, Trujillo, January - July 2016. Materials and Methods: It was carried out an experimental in vitro, cross-sectional study where the antifungal efficacy of the garlic solution and colloidal oats was tested, in comparison with clotrimazole against the growth of Candida albicans, Trujillo, January - July 2016. Statistical and analytical analyzes were carried out . Results: The efficacy of the garlic solution from 40% to 90% is evidenced, the latter being of similar efficacy as the 500mg clotrimazole. No antifungal action is evidenced in the colloidal oatmeal solution. Conclusions: The antifungal effectiveness of the garlic solution and Clotrimazole on Candida albicans strains is demonstrated; However, null antifungal effectiveness is reported with respect to the colloidal oatmeal solution against the strains indicated above.